PENGARUH KUALITAS PELAYANAN MOBILE BANKING TERHADAP KEPUASAN NASABAH PADA BANK BNI KANTOR CABANG PEMBANTU DUREN TIGA JAKARTA - Putri Sarirati; Nanda Syafira Ardini (Equilibrium Point : Jurnal Manajemen dan Bisnis, 2024)
The sampling technique used in this research was the author's use of random samplingtechnique or by random method, all employees were a population of 162 and weresampled using the Slovin formula in Husein Umar, 2017, obtaining only 62 samples.Based on the results of the regression analysis, it turns out that the mobile bankingservice quality variable can significantly increase customer satisfaction, the equationvalue Y = 7.298 + 0.777 the ttable value in (60) is = 1.671, then Ho is rejected andHa is accepted, meaning there is evidence that mobile banking service quality has avery significant influence on customer satisfaction. Based on the analysis results, thereis a positive influence of mobile banking service quality on customer satisfaction, avalue of 0.844 is obtained, so it can be concluded that the influence is very strong orthe Coefficient of Determination (KD) value is: 71.2%.